La función social de la propiedad: la recepción de León Duguit en Colombia - Batista Pereira, Eliécer (2023)
This article examines th e local reception of Leon Duguit’s theory on the social function of property. The paper will begin by comparing the transnational theory that played an important role in the law of the center, through Duguit, to the ways in which this theory was construed in Colombia, both in private law and public law. The article will study the main debates that occurred during the process of constitutional reform of 1936, as well as the bill for Act 200 of the same year. The main figures in those legislative debates will be presented, with the purpose of describing local reception, especially in public law. Finally, the article will discuss the influence of property as a social function in private law, specifically in the way this concept was used by the Colombian Supreme Court between 1936 and 1940.